Punitive application in Algerian legislation - Bouidane, Nora; Chaaoua, Mehdi (Journal of Human Sciences, 2022)
Algeria seeks to develop the penal system by developing the process of punitive execution by adopting methods aimed at achieving its objectives represented in the establishment of convicts, social and health care, as well as by receiving disciplinary programs and evaluation such as job evaluation . Methods that are humiliating outside of it, like parole and other regulations, and this has been confirmed by rule 66 of the minimum set of rules for the treatment of prisoners, and Algeria thus keeps pace with international developments in the field of the application of sanctions.